HUBUNGAN PENYESUAIAN DIRI DENGAN PRESTASI BELAJAR MAHASISWA TAHUN PERTAMA DI FAKULTAS DAKWAH DAN ILMU KOMUNIKASI UIN IMAM BONJOL PADANG - Reza Febra Yeni; Eliza Eliza; Afnibar Afnibar (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Inability to get to know the environment of newly entered educational institutions, for students will slow down the continuity of the learning process. Individuals entering a new environment need to adjust quickly. Orientation should accelerate student adjustment. However, the phenomenon that occurs is that there are still students who have difficulty in adjusting to influence their learning outcomes, such as the presence of students who are not dressed according to the rules, ashamed to speak in public, and the habit of playing truant during lectures. Because it is necessary to do research on the relationship of adjustment to learning achievement. This study aims to get a picture of self-adjustment, learning achievement and the relationship between the two in the first year 2016 batch of Da'wah and UIN IB Communication Studies in Padang. This research uses quantitative methods with correlational research types. The results showed that most of the first year students had the ability to adapt and have good learning achievements. There is a positive and significant relationship between adjustment to learning achievement, meaning that the higher the ability to adjust the higher the student's learning achievement.